An unusual case of childhood sarcoidosis - KARADAĞ, BÜLENT TANER; ERDEM ERALP, ELA; KIYAN, GÜRSU; KAYA, HANDAN; GÖKDEMİR, YASEMİN (SOC ARGENTINA PEDIATRIA, 2013)
Sarcoidosis is a systemic granulomatous disease of unknown etiology that may affect many systems, mainly lungs. Most of the patients present at stages I and II lung involvement. Pulmonary infiltrates without hilar lymphadenopathy (state III) rarely occurs. Extrapulmonary organ involvement is common in pediatric sarcoidosis. The aim of this report is to present an unusual case of childhood sarcoidosis with stage III lung involvement without any extrapulmonary organ involvement. A 7-year-old girl presented with the complaints of malaise, fatigue, weight loss and dyspnea. There was patchy, bilateral ground glass view at high resolution computer tomography. Video assisted thoracoscopic lung biopsy was performed and histopathological examination showed nonnecrotising epitheloid-cell granulomas with giant cells. She did not have any hilar or extrapulmonary organ involvement and pulmonary sarcoidosis at stage III was diagnosed. Sarcoidosis should be considered in the differential diagnosis of children with interstitial lung disease.
Keywords: childhood; interstistial lung disease; sarcoidosis; pulmonary involvement; PULMONARY SARCOIDOSIS; CHILDREN